2020
DOI: 10.1126/sciadv.abd3590
|View full text |Cite
|
Sign up to set email alerts
|

Gene reuse facilitates rapid radiation and independent adaptation to diverse habitats in the Asian honeybee

Abstract: Animals with recent shared ancestry frequently adapt in parallel to new but similar habitats, a process often underlined by repeated selection of the same genes. Yet, in contrast, few examples have demonstrated the significance of gene reuse in colonization of multiple disparate habitats. By analyzing 343 genomes of the widespread Asian honeybee, Apis cerana, we showed that multiple peripheral subspecies radiated from a central ancestral population and adapted independently to diverse habitats. We found strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 65 publications
15
95
0
Order By: Relevance
“…Although AML and ACC are close relatives with similar basic biology, some behavioral differences have evolved since their speciation [78]. AML and ACC share the age-based division of labor, with younger bees specializing on nursing before maturing to foraging activities [79] and ACC foragers also specialize in nectar or pollen collection [28,80] similar to AML [27]. Accordingly, we found the main differences of stimulus responsiveness and TRPs expression among worker phenotypes conserved.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although AML and ACC are close relatives with similar basic biology, some behavioral differences have evolved since their speciation [78]. AML and ACC share the age-based division of labor, with younger bees specializing on nursing before maturing to foraging activities [79] and ACC foragers also specialize in nectar or pollen collection [28,80] similar to AML [27]. Accordingly, we found the main differences of stimulus responsiveness and TRPs expression among worker phenotypes conserved.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, foragers often specialize on collecting only one of the principal food sources, pollen or nectar [27]. Specialized nurses, nectar foragers and pollen foragers are also found in the closely-related Eastern honeybee, Apis cerana [28], thus offering a suitable parallel system for our study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since orthologs of LKRs have been identified in five sequenced bee genomes, it is likely that LK signaling is present in these hymenopterans, but not in ants [62,72]. In support of the importance of LK signaling in honeybees, a recent paper showed that the lkr gene influences labor division in foraging for pollen and nectar in the Asian honeybee (Apis cerana) [73].…”
Section: Leucokinins and Their Receptors In Insects And Other Invertementioning
confidence: 99%